2017
DOI: 10.1007/s11739-017-1608-x
|View full text |Cite
|
Sign up to set email alerts
|

CHADS2, CHA2DS2-VASc and R2CHADS2 scores predict mortality in patients with coronary artery disease

Abstract: Few studies to date address the predictive ability of CHADS-VASc and RCHADS in CAD patients. Our aim is to investigate the prognostic performance of CHADS, CHADS-VASc and RCHADS scores in patients with coronary artery disease (CAD). Angiographically obstructive CAD patients were enrolled. The prognostic performance of the three risk scores was evaluated using Cox hazards models. In addition, we compared their predictive values by calculating C statistics, net reclassification improvement (NRI) and integrated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“… 15 In a recent study, Huang et al enrolled 3,295 subjects with CAD and found that R 2 CHADS 2 had comparable predictive ability of mortality to the Global Registry of Acute Coronary Events score. 16 Compared with the CHADS 2 score (c-statistic =0.61), the R 2 CHADS 2 (c-statistic =0.66, p <0.05) score provides better discrimination for mortality. The results of this study suggested that the R 2 CHADS 2 score could be used to predict composite events for patients with CAD, and the AUC of the R 2 CHADS 2 was statistically larger than of the CHADS 2 score.…”
Section: Discussionmentioning
confidence: 90%
“… 15 In a recent study, Huang et al enrolled 3,295 subjects with CAD and found that R 2 CHADS 2 had comparable predictive ability of mortality to the Global Registry of Acute Coronary Events score. 16 Compared with the CHADS 2 score (c-statistic =0.61), the R 2 CHADS 2 (c-statistic =0.66, p <0.05) score provides better discrimination for mortality. The results of this study suggested that the R 2 CHADS 2 score could be used to predict composite events for patients with CAD, and the AUC of the R 2 CHADS 2 was statistically larger than of the CHADS 2 score.…”
Section: Discussionmentioning
confidence: 90%
“…[11] It has also been suggested that CHA2DS2-VASc score can provide prognostic information for ischemic events and mortality in patients with coronary artery disease, in patients undergoing PCI and in patients undergoing CABG surgery. [24][25][26][27] For this reason, the components of CHA2DS2-VASc score may be associated with increased ischemic risk, thrombotic risk, atherosclerotic process and micro vascular dysfunction, all of which take part in the mechanism and pathogenesis of no-reflow. [19,28,29] Similar to our study, studies investigating the effect of the CHA2DS2-VASc score on predicting no-reflow in ST segment elevated MI patients undergoing primary PCI have also found a relation between them.…”
Section: Discussionmentioning
confidence: 99%
“…CHADS2 and CHA 2 DS 2 -VASc scores are clinical thromboembolic risk scores for predicting stroke in patients from the high-risk population and with non-valvular AF [13]. However, recent studies have demonstrated that both scores can predict mortality in various cardiovascular diseases, irrespective of the presence of AF [14,15]. In our study, the subjects with PH had significantly higher CHA 2 DS 2 -VASc and CHADS2 scores com-pared to the normal pulmonary pressure group.…”
Section: Discussionmentioning
confidence: 99%